The Relationship between Academic Rational Belief and Student Engagement among Senior High School Students - Wisherly Musagaros; Silvi Juwita (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Student engagement is an important indicator of learning quality because it reflects students’ behavioral, emotional, and cognitive involvement in the learning process. Although student engagement has been widely discussed in previous studies, research specifically examining its relationship with academic rational belief among senior high school students remains limited. This study aims to analyze the relationship between academic rational belief and student engagement among eleventh-grade students at SMA Negeri 13 Padang. A quantitative approach with a correlational design was employed, involving 356 eleventh-grade students selected using total sampling. Data were collected using the Student Engagement Scale and the Academic Rational Beliefs Scale, then analyzed using descriptive statistics, normality testing, linearity testing, and Pearson Product Moment correlation with the assistance of SPSS. The findings show that both student engagement and academic rational belief were generally in the moderate category. Correlation analysis revealed a significant positive relationship between academic rational belief and student engagement, with a correlation coefficient of r = 0.619 and a significance value of p < .001. These results indicate that students with higher academic rational belief tend to demonstrate higher engagement in learning activities. This study contributes to the development of student engagement literature by emphasizing academic rational belief as an internal cognitive factor associated with students’ learning involvement. Practically, the findings imply that schools, teachers, and counselors should strengthen students’ rational academic beliefs through counseling services, reflective learning activities, and adaptive learning strategies.